Stock Option: Perlakuan Akuntansi dan Pengaruhnya Terhadap Earning Per Share - ~ Muliawati (Bina Ekonomi, 2001)
This paper discusses some recognition methods for stock compensation and how stock compensation dilutes earning per share. Some methods discussed in this paper are fair value Method' and intrinsic value method. The mechanism of how stock compensation dilutes earning per share is also explained at the end of in this paper.